PENGARUH UMUR DAN POSISI LETAK RUAS PADA BATANG TERHADAP SIFAT PENGERINGAN TIGA JENIS BAMBU - Efrida Basri; Saefudin Saefudin (Jurnal Penelitian Hasil Hutan, 2004)
Bamboo is an important multipurpose plant in Indonesia. It is widely used in industry, construction. furniture, and other purposes. As a raw material like solid wood, bamboo needs to be dried. Proper drying can minimize its dimensional changes during usage. improve strength, and eliminate other processing defects. This study was intended to examine influence of age and culm position on drying properties of three bamboo species, i.e. mayan (Gigantochloa robusta Kurz), tali (Gigantochloa apus Kurz). and hitam (Gigantochloa atroviolacea). The most optimum drying temperature for the three species was also determined in this study. Determination of drying schedule was initially explored using medium temperature (80°C) and observing visual defects that may generate during drying, i.e. splits/cracks, and concave or collapse.Results showed that drying properties of each bamboo species were affected by the age and the culm position. The older tree age and the closer the culm location to the top porsion then the lower the shrinkage. Immature culm had a higher drying rate than the mature one, but it had a lower quality. The most suitable drying temperature for those bamboos was ranging about 30 -50°C. The proper drying temperature, however, still needs, further trials prior to any usage for commercial operation.